Philosophy of Education: Overcoming the Theory-Practice Divide - Laverty, Megan (Paideusis, 2006)
I argue that philosophy has a dual role in teacher education: first, it prompts teachers to take individual responsibility for and become more reflective about the values expressed by their teaching practices so as to enable them to teach with greater authenticity; second, it provides teachers with a disciplinary technique that is useful in the facilitation of student reflection and dialogue so as to enable students to think and live more authentically. In this paper, I focus on the former and suggest that because teaching practices are expressions of values, teachers need to become more aware of competing conception of the human good(s)—including their own—and how these inform their relationship to disciplinary expertise, educational institutions, and teaching. I argue that authentic teaching necessitates: a conviction that individuals are improved, as human beings, by what it is they study; a deepening engagement with what this conviction means; and a commitment to its truth by way of how one engages with one’s discipline and students. It is in this regard that I explore Plato’s dialogue Gorgias, in particular, the example of Socrates, his conversations with Callicles, as well as his distinction between sophistry/pandering and educating/healing. In the final part of the paper, I argue that, assuming I am correct about the necessity and value of teaching authentically, philosophy—conceived of as honest, rigorous, ongoing, open-ended and dialogical engagement with our convictions—should be an integral part of any good teacher education program.